The Value and Evaluation of Educational Environments: The Case of Lithuanian General Education Schools - Survutaitė, Dalia (Pedagogika, 2024)
Educational environments include different physical places, contexts, and cultures in which pupils are raised and learn. This article offers a retrospective view of the importance and significance of educational environments. Gradually, educational leaders, together with their communities, are reflecting on the adequacy of existing educational environments and acknowledging the necessity to update, adjust and create new ones.